2021
DOI: 10.1186/s12916-021-02042-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of functional fitness, antibodies to SARS-CoV-2 and immunological indicators within 1 year after discharge in Chinese health care workers with severe COVID-19: a cohort study

Abstract: Background Few studies had described the health consequences of patients with coronavirus disease 2019 (COVID-19) especially in those with severe infections after discharge from hospital. Moreover, no research had reported the health consequences in health care workers (HCWs) with COVID-19 after discharge. We aimed to investigate the health consequences in HCWs with severe COVID-19 after discharge from hospital in Hubei Province, China. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Among the 193 studies under full-text review, 153 studies were excluded. Eventually, 40 studies were included in this meta-analysis based on the inclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 193 studies under full-text review, 153 studies were excluded. Eventually, 40 studies were included in this meta-analysis based on the inclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, the project has carried out follow-up studies up to 1 year after discharge. The assessed variables include: organ impairment, persistent symptoms, psychological problems, physical examinations, and consultation with academicians [ 19 ]. In this study, HCWs with mild or severe COVID-19 in Wuhan, China, who were discharged from the hospital 1 year prior to this study were invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were from the "Rehabilitation Care Project for Medical Staff Infected with COVID-19" in China, it was launched by the Chinese Academy of Engineering and Tencent Charity Foundation (Xiong et al, 2021). The participants were HCWs with COVID-19 in Hubei Province (including the provincial capital city Wuhan and its surrounding cities).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…A study in China followed HCWs with COVID-19 for 3 months after discharge, it suggested that 69 (91%) of the HCWs with COVID-19 had returned to their original work, 82% of the HCWs' lung HRCTs returned to normal, and 42% of the HCWs had mild pulmonary function abnormalities (Liang et al, 2020). Our previous study reported dynamic changes of functional fitness and immunological indicators within 1 year after discharge in HCWs with severe COVID-19 (Xiong et al, 2021). There were also other studies revealing recovery of functional fitness (Paz et al,7 2021), lung function (Huang et al, 2021) and immune function (Qin et al, 2020;Wan et al, 2020) in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 98%